Development of student worksheets (LKS) based on the synergy of teachers of the Qur'an, Hadith, and Creed and Moral in cultivating the spirituality of students at Madrasah Al-Iyah Mutiara Aulia - Salsabilla Utami; Mardianto Mardianto (Universitas Muhammadiyah Enrekang, 2025)
This study aims to identify the synergy between Al-Qur'an Hadith and Akidah Akhlak teachers in fostering students' spirituality at Mutiara Aulia Islamic Senior High School. This study uses a descriptive qualitative approach with a case study approach. Data collection techniques in this study through interviews, observation and documentation. Data analysis techniques in this study consist of data collection (data reduction), data presentation (display), and drawing conclusions (verification). Based on the research results obtained from interviews and observations, the synergy between Al-Qur'an Hadith and Akidah Akhlak teachers in fostering students' spirituality at Mutiara Aulia Islamic Senior High School has been running well. This can be seen from the religious activity program that has been programmed and runs smoothly, although there are still some gaps between the two teachers and some activity facilities that have not been met. Religious activities carried out at Mutiara Aulia Islamic Senior High School such as congregational prayer, Al-Qur'an recitation and routine studies carried out into internalize Islamic values in everyday life have had a positive impact on students.